Impact of Revenues from Oil and Non-Oil Sectors on the Economic Growth of Azerbaijan - Huseynli, Nigar (International Journal of Energy Economics and Policy, 2022)
The main purpose of the study is to determine the relationship between the revenues obtained from the oil and non-oil sectors of Azerbaijan, which is a country dependent on the oil industry, and its economic growth. The fact that Azerbaijan is an oil-dominated country and a large part of its exports consist of oil may have caused us to think that the share of oil in the country’s incomes will be higher. However, the fact that the country generally exports oil in crude form and imports it ready-made affects the final result. In this study, the share of the oil and non-oil sectors in the economic growth of the country over a 20-year period is determined. Another aim of the study is to reveal how the earnings from these two different sectors affect the employment level of the country. During the study, the logarithm of the variables was taken and included in the analysis in order to measure the strong relationship between the data. According to the results obtained, the development of these sectors affects the decrease in unemployment levels and has be a positive result between the realized economic growth and oil revenues and non-oil sector revenues.